A clinical trial with protracted infusion 5‐fluorouracil and mitomycin C for localized squamous cell carcinoma of the anus. Issue 1 (9th December 2018) - Ngan, David; Chu, Julie; Chander, Sarat; Michael, Michael; Heriot, Alexander G.; Ngan, Samuel Y.; Rischin, Danny; Leong, Trevor
Abstract: Purpose: Mitomycin C (MMC) plus standard 5‐fluorouracil (FU) infusion in weeks 1 and 5 often contributes to radiotherapy interruptions and possibly less‐than‐ideal outcomes in anal cancer. This study was to evaluate alternative strategies for chemotherapy delivery that might be less toxic or more efficacious, and outcomes of patient‐initiated treatment interruption for severe acute toxicity. Materials and methods: This was a prospective, nonrandomized study for patients with T1‐4N0‐3M0 anal squamous carcinoma. Radiotherapy of 54 Gy in 30 fractions over 6 weeks was given with infusion FU 300 mg/m 2 /day for 96 hours/week for 6 weeks plus bolus MMC at 10 mg/m 2 on D1. Results: Fifty patients were recruited (72% female). Median age was 60.5 years (35–84). Forty‐seven patients (94%) received 54 Gy. Median duration of chemoradiation was 39 days (37–105). Grade 3 and 4 acute toxicity were observed in 66%. Thirty‐one percent with severe acute toxicity developed severe late toxicity. Of those who experienced severe late skin toxicity, 29% did not have severe acute toxicity. Disease‐free survival at 5 years was 74% (95% confidence interval [CI], 60–84), and at 9 years 61% (95% CI, 46–74). Overall survival at 5 years was 84% (95% CI, 71–92), and at 9 years 67% (95% CI, 50–81). Colostomy‐free survival at 5 years was 70% (95% CI, 56–81), and at 9 years 57% (95% CI, 40–72). Conclusion: It is feasible to deliver chemoradiation with bolus MMC and protracted infusion FU for anal cancer. Efficacy and toxicity of this regimen seem similar to conventional chemoradiation with FU/MMC. Acute skin toxicity is not a reliable predictor of severe late skin toxicity.